Age biases the judgment rather than the perception of an ambiguous figure - Ambroos Brouwer (Nature Portfolio, 2021)
Abstract Older participants who are briefly presented with the ‘my wife/mother-in-law’ ambiguous figure estimate its age to be higher than young participants do. This finding is thought to be the result of a subconscious social group bias that influences participants’ perception of the figure. Because people are better able to recognize similarly aged individuals, young participants are expected to perceive the ambiguous figure as a young woman, while older participants are more likely to recognize an older lady. We replicate the difference in age estimates, but find no relationship between participants’ age and their perception of the ambiguous figure. This leads us to conclude that the positive relationship between participants’ age and their age estimates of the ambiguous ‘my wife/mother-in-law’ figure is better explained by the own-age anchor effect, which holds that people use their own age as a yard stick to judge the age of the figure, regardless of whether the young woman or the older lady is perceived. Our results disqualify the original finding as an example of cognitive penetrability: the participants’ age biases their judgment of the ambiguous figure, not its perception.